2020
DOI: 10.1039/d0ob00106f
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised thermally induced phase separation (TIPS) microparticles enabled for “click” chemistry

Abstract: In this study we describe a novel platform for generating functionalised TIPS microparticles for “click” conjugation to various active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The monobromo derivative was selective for cysteine residues (Z HER2:2395 –Cys) and the dibromo for disulfide bridges (Ontruzant, Ontruzant Fab). [ 54 ] See Figure S21 in the Supporting Information for chemical structures of both pyridazinedione linkers. Previous work by Bahou and Chudasama have shown that these linkers have negligible impact on stability and antigen binding.…”
Section: Resultsmentioning
confidence: 99%
“…The monobromo derivative was selective for cysteine residues (Z HER2:2395 –Cys) and the dibromo for disulfide bridges (Ontruzant, Ontruzant Fab). [ 54 ] See Figure S21 in the Supporting Information for chemical structures of both pyridazinedione linkers. Previous work by Bahou and Chudasama have shown that these linkers have negligible impact on stability and antigen binding.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 33 Furthermore, TIPS PLGA microcarriers have been broadly characterized for various applications, which include myogenesis-related studies. 11 , 12 , 34–36 The work reported herein is the first to combine these areas of expertise to prepare a tissue-engineered combined product with the goal of treating fecal incontinence. This condition still misses a reliable treatment highly due to the inefficient cell delivery typically used in Regenerative Medicine approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Another key application that has benefited from employing PD-based bioconjugation strategies, is the formation of nanoparticle-antibody conjugates. 5,61,62 DiBrPDs in particular have been used extensively to site-selectively re-bridge antibody-fragments, which can then be attached to the surface of nanoparticles through efficient copper free "click" chemistries. Previous reports have shown that antibody-nanoparticle conjugates synthesised with antibody fragments (e.g.…”
Section: Orientated Nanoparticle-antibody Decorationmentioning
confidence: 99%